2007
DOI: 10.1590/s0034-70942007000500005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da eficácia analgésica pós-operatória de 20, 30 ou 40 mL de ropivacaína no bloqueio de plexo braquial pela via posterior

Abstract: -Estudo Comparativo da Eficácia Analgésica Pós-Operatória de 20, 30 ou 40 mL de Ropivacaína no Bloqueio de Plexo Braquial pela Via Posterior. JUSTIFICATIVA E OBJETIVOS:As intervenções cirúrgicas por via artroscópica no ombro estão relacionadas com a dor pós-operatória de grande intensidade. Dentre as técnicas de analgesia, o bloqueio do plexo braquial é a que oferece os melhores resultados. O objetivo deste estudo foi determinar qual volume de anestésico local no bloqueio de plexo braquial pela via posterior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
(16 reference statements)
0
8
0
3
Order By: Relevance
“…Different volumes of anesthetic have already been employed, but there is no definition of the ideal volume. It was evident that posterior brachial plexus block with 20 mL, 30 mL, and 40 mL of 0.375% ropivacaine offerered the same analgesic efficacy in the postoperative period of arthroscopic surgeries of the shoulder 27 . Similarly, it was observed that the increase in concentration from 0.5% to 0.75% when 30 mL of ropivacaine were employed in the interscalene brachial plexus block did not show benefit in the postoperative analgesia of surgeries of the shoulder 22 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Different volumes of anesthetic have already been employed, but there is no definition of the ideal volume. It was evident that posterior brachial plexus block with 20 mL, 30 mL, and 40 mL of 0.375% ropivacaine offerered the same analgesic efficacy in the postoperative period of arthroscopic surgeries of the shoulder 27 . Similarly, it was observed that the increase in concentration from 0.5% to 0.75% when 30 mL of ropivacaine were employed in the interscalene brachial plexus block did not show benefit in the postoperative analgesia of surgeries of the shoulder 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the posterior brachial plexus block, also known as paravertebral cervical block, has received wide attention [1][2][3]7,27,28 . Different volumes of anesthetic have already been employed, but there is no definition of the ideal volume.…”
Section: Discussionmentioning
confidence: 99%
“…A técnica de bloqueio do plexo braquial, por via interescalênica, descrita por Winnie (abordagem lateral) é a mais utilizada para intervenções cirúrgicas no ombro [5][6][7][8][9] . Algumas alternativas à técnica de Winnie têm sido propostas, dentre elas, a abordagem do plexo braquial pela via posterior se demonstrou ser segura e eficaz [9][10][11][12][13][14][15][16] . Em estudo anterior, foi observado que a utilização de volumes de anestésico de 20, 30 ou 40 mL na abordagem posterior promove analgesia pós-operatória semelhante 13 .…”
Section: Discussionunclassified
“…Algumas alternativas à técnica de Winnie têm sido propostas, dentre elas, a abordagem do plexo braquial pela via posterior se demonstrou ser segura e eficaz [9][10][11][12][13][14][15][16] . Em estudo anterior, foi observado que a utilização de volumes de anestésico de 20, 30 ou 40 mL na abordagem posterior promove analgesia pós-operatória semelhante 13 . No presente estudo, confirmou-se a hipótese de que altas concentrações de ropivacaína no bloqueio de plexo braquial pela via posterior associadas a antiinflamatórios não-esteróides e dipirona promovem analgesia prolongada após intervenções cirúrgicas por via artroscópica no ombro.…”
Section: Discussionunclassified
See 1 more Smart Citation